Parent recommendation to bank sperm among at‐risk adolescent and young adult males with cancer. Issue 10 (26th May 2020) - Flynn, Jessica S.; Russell, Kathryn M.; Lehmann, Vicky; Schenck, Lauren A.‐M.; Klosky, James L.
Abstract: Background: Adolescent and young adult (AYA) males newly diagnosed with cancer are often faced with making quick decisions about whether to cryopreserve ("bank") sperm prior to treatment initiation. Given that parental influence is crucial among young patients, the present study examines the prevalence of and factors associated with parent recommendation to bank sperm. Procedure: Parents of 13‐ to 21‐year‐old males newly diagnosed with cancer and at risk for infertility secondary to impending gonadotoxic treatment completed questionnaires typically within one week of treatment initiation. Medical and sociodemographic data, communication factors, and psychological factors were considered in a logistic regression model of parent report of parental recommendation to bank sperm (yes/no). Results: Surveys from 138 parents (70.3% female) of 117 AYA males (mean age = 16.1 years, SD = 2.0) were analyzed. Over half of parents recommended banking to their sons ( N = 82; 59.4%). Parents who received a provider recommendation to bank sperm (odds ratio [OR] = 18.44, 95% confidence interval [CI], 4.20‐81.01, P < 0.001) or who believed in the benefits of banking (OR = 1.22, 95% CI, 1.02‐1.47, P = 0.03) were significantly more likely to recommend sperm banking. Conclusions: Given parents' role in influencing sperm banking outcomes, provider recommendation and promotion of banking benefits may influence parents and empower initiation of these sensitive discussions with their sons. Utilization of this approach should yield beneficial outcomes regardless of the banking decision.